Relationship Among Body Mass Index, Physical Activity, and Dietary Habit Students - Devi, Ni Putu Shinta Ayu; Rahayuni, Kurniati; Widiawati, Prisca (STKIP PGRI Jombang, 2023)
This study aims to determine the relationship between body mass index (BMI), physical activity, and dietary habits of students at SMPN 1 Karangploso. This study used several analyses’ such as the Shapiro-Wilk normality test, linearity test, multicollinearity test, heteroscedasticity test, bivariate analysis using simple regression test, and multivariate analysis using multiple regression test. The simple linear regression resulted from 2 models that showed how strong the relationship between physical activity on BMI and dietary habits on BMI is. The model results were respectively and those models indicated a negative relationship between physical activity on BMI and a positive relationship between dietary habit on BMI. While resulting from a model relationship towards BMI value along with a positive relationship between dietary habit and BMI value. Since it got an R-value of 0,754, this result is accurate enough. In conclusion, according to the regression methods used in this study, there is a real relationship between physical activity, dietary habits, and BMI values. Thus, it means that physical activity and dietary habits have an influence on determining overweight status in 13-15-year-old boys and girls.